2023
DOI: 10.1136/bmjgast-2023-001184
|View full text |Cite
|
Sign up to set email alerts
|

EUS-guided through the needle microbiopsy: a useful adjunct in the investigation of pancreatic cystic lesions

Abstract: ObjectiveEndoscopic ultrasound-guided through-the-needle microbiopsy (EUS-TTNB) forceps is a recent development that facilitates sampling of the walls of pancreatic cystic lesions (PCL) for histological analysis. We aimed to assess the impact of EUS-TTNB and its influence on patient management in a tertiary pancreas centre.DesignA prospective database of consecutive patients who underwent EUS-TTNB from March 2020 to August 2022 at a tertiary referral centre was retrospectively analysed.ResultsThirty-four patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…EUS-TTNB is one of the most recent and promising techniques for the definition of PCLs, with excellent technical success (98.5%, CI 97.3-99.6%) and high accuracy (86.7%, CI 80.1-93.4) according to a recent metanalysis [15]. Several studies have compared TTNB to standard EUS-FNA, with conventional fluid analysis demonstrating the clear superiority of TTNB in risk stratification and its ability to provide a specific diagnosis [8,9,[11][12][13][38][39][40][41][42][43][44][45][46][47][48]. Moreover, a study demonstrated that EUS-TTNB specimens are suitable for molecular analyses [49].…”
Section: Discussionmentioning
confidence: 99%
“…EUS-TTNB is one of the most recent and promising techniques for the definition of PCLs, with excellent technical success (98.5%, CI 97.3-99.6%) and high accuracy (86.7%, CI 80.1-93.4) according to a recent metanalysis [15]. Several studies have compared TTNB to standard EUS-FNA, with conventional fluid analysis demonstrating the clear superiority of TTNB in risk stratification and its ability to provide a specific diagnosis [8,9,[11][12][13][38][39][40][41][42][43][44][45][46][47][48]. Moreover, a study demonstrated that EUS-TTNB specimens are suitable for molecular analyses [49].…”
Section: Discussionmentioning
confidence: 99%